Keep Calm and Say Sorry!: The use of Apologies by EFL Teachers in Turkish and English - Zeynep Canli; Bekir Canli (Educational Process: International Journal)
The aim of the study is to investigate apology strategies used by EFL teachers in Turkish and English. For the purpose of the study, a qualitative research was carried out. The study utilized purposeful sampling. Three EFL instructors participated in this study. The data were collected via a Discourse Completion Task (DCT) that had eight apology situations. Analyzing the results indicated that there was no significance difference in apology strategies used by the participants, and their L1 apology speech act strategies were not significantly different from their L2 productions. Their L1 can be said to have an effect on their use of apologies, as they transferred native Turkish norms into English. The results of the study emphasized the importance of teaching pragmatic competence in EFL. This study might be of pedagogical help and significance to teachers interested in pragmatics in general, and apology speech act in particular.